The Implementation of the Link and Match Program Between Vocational High Schools and the Business-Industrial Sectors - Oktasari Wardia Ningsih; Suyatno Suyatno; Enung Hasanah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
Learning in Vocational High Schools aims to produce graduates who are job-ready with skills relevant to their vocational fields. However, there remains a mismatch between graduates' competencies and labor market demands, exacerbated by limited practical facilities and weak synergy between schools and the business and industrial sectors (DUDI). The revitalization program for vocational schools through the link and match approach was launched to address this issue by emphasizing curriculum alignment and intensive collaboration with industry. This study aims to examine the implementation of the link and match program at SMK Negeri 1 Pengasih, Bantul, Yogyakarta. A qualitative approach was employed, with data collected through interviews, observations, and documentation. The findings indicate that the implementation of link and match at SMK Negeri 1 Pengasih has been systematically carried out through industry-based curriculum alignment, industrial work practice, training for vocational teachers, Memorandums of Understanding (MoUs) with industry partners, and competency-based skill assessments. The program has succeeded in enhancing graduates' competencies and competitiveness, although it faces challenges such as limited internship quotas, differing industry standards, and inadequate practical facilities. Strong collaboration among schools, industries, and the government is essential for success, with recommendations including improved facilities and strengthened partnerships to optimize the program’s effectiveness.